2022
DOI: 10.1021/acs.analchem.2c02905
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Quantification of Pharmaceuticals via 1H Solid-State NMR Spectroscopy

Abstract: The physicochemical properties of active pharmaceutical ingredients (APIs) can depend on their solid-state forms. Therefore, characterization of API forms is crucial for upholding the performance of pharmaceutical products. Solid-state nuclear magnetic resonance (SSNMR) spectroscopy is a powerful technique for API quantification due to its selectivity. However, quantitative SSNMR experiments can be time consuming, sometimes requiring days to perform. Sensitivity can be considerably improved using 1H SSNMR spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 68 publications
0
5
0
Order By: Relevance
“…6–16 Unfortunately, the intrinsically low sensitivity of NMR may limit the opportunity to detect a minor polymorphic phase in a mixture with a major polymorphic phase. 17–19…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…6–16 Unfortunately, the intrinsically low sensitivity of NMR may limit the opportunity to detect a minor polymorphic phase in a mixture with a major polymorphic phase. 17–19…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8][9][10][11][12][13][14][15][16] Unfortunately, the intrinsically low sensitivity of NMR may limit the opportunity to detect a minor polymorphic phase in a mixture with a major polymorphic phase. [17][18][19] Interestingly, recent advances in dynamic nuclear polarization (DNP) NMR, [20][21][22][23][24][25][26][27] in which polarization from the electron spin of an exogenous polarizing agent [28][29][30][31][32] is transferred to nuclear spins through microwave irradiation, can signicantly enhance the ability of NMR to detect small amounts of solid phases in heterogenous materials by enhancing the sensitivity of solid-state NMR measurements by several orders of magnitude. Furthermore, DNP NMR may also generate large polarization gradients, allowing domain sizes between ca.…”
Section: Introductionmentioning
confidence: 99%
“…[26][27][28] Emerging studies have demonstrated the advantages of fast and ultrafast MAS for the characterization of pharmaceutical materials. 17,20,26,[29][30][31][32][33][34][35] For instance, Lu et al investigated the molecular packing of POSA crystals using 1 H ssNMR at a MAS rate of 110 kHz. 17 Polenova and coworkers studied the structure of a fluorine-containing drug, mefloquine, using 19 F methods under fast MAS.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Further reduction in the line width by imporoved homonuclear decoupling schemes would allow a broader use of proton solid-state NMR to applications especially in small molecules and pharmaceuticals. [3][4][5] The total observed line width in experimental NMR spectra is determined by several different contributions. Following the convention introduced by Maricq and Waugh 6 , one usually distinguishes the inhomogeneous and the homogeneous broadening.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Further reduction in the line width by imporoved homonuclear decoupling schemes would allow a broader use of proton solid-state NMR in applications especially for small molecules and pharmaceuticals. 3–5…”
Section: Introductionmentioning
confidence: 99%